DIFFRACTION COEFFICIENTS AND FIELD PATTERNS OF OBTUSE ANGLE DIELECTRIC WEDGE ILLUMINATED BY E-POLARIZED PLANE-WAVE - KIM, SY (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1992)
The diffraction problem is treated for the incidence of an E-Polarized plane wave on both interfaces of an obtuse-angled dielectric wedge. Based on the dual integral equation, the total field is obtained by sum of the physical optics solution and the edge-diffracted correction term. Calculated diffraction coefficients and field patterns are plotted in figures for wedge angle 120-degrees, incident angles 60-degrees and 70-degrees, and relative dielectric constants 2 and 10. It is shown that the Neumann expansion to the nonuniform currents provides a more accurate correction to the physical optics currents than the multipole expansion as the angle of dielectric wedge increases.